Tsuur and khumei in the sources of oral culture - L. Kherlen (Nomadic Civilization: Historical Research, 2021)
There are many sources of Mongolian music in Mongolian and Chinese oral and written sources, including the Tsuur. ” Echoes cannot be imagined without the organ of speech, and this is the main feature of their color imitation. This is because the evidence that a person used to imitate the sound of music before making music and then used his or her speech organs as music can be clearly seen in Mongolian throat singing and whistling. The percussion music retains elements of both the harmonica and the whistle in the structure of the melody, and the percussion method is based on the whistle. Even today, it is interesting to see when and where the percussion was played and in what order. It is not used for small weddings, love affairs, or music, but is usually used only for large ovoo rituals and large-scale festivals. We are proud that this tradition has been preserved in an almost ancient form and passed down to us. It also needs to be preserved and developed, and the source material is still open.